Estimation of the Recyclable Waste amount Collected by Informal Recycling Shops: Case Study in Nay Pyi Taw, Myanmar: 10.32526/ennrj/19/2020157 - Ko, Chit Oo; Tun, Ye; Lwin, Naing Htet; Moe, Thazin; Eaindray, Juu (Environment and Natural Resources Journal, 2021)
The study investigates and estimates the type and amount of recyclable waste collected by informal recycling shops in Nay Pyi Taw by using face to face interview for 23 informal recycling shops in Nay Pyi Taw in May 2020. The descriptive statistics (frequency and percentage) and inferential statistics (two-sample paired t-test and Pearson’s correlation) were applied. According to the results, the average estimated waste amount collected by each recycling shop per day before and during the novel coronavirus (COVID-19) pandemic was 1,798 kg (Min. 0 to Max. 1,401 kg) and 856 kg (Min. 0 to Max. 892 kg), respectively. As a result of this study, it can be seen that the amount of daily collected waste has a positive relationship with the daily income of recycling shops, and COVID-19 has impacted the income of informal recycling shops. According to the results, getting an official license, financial problems, and limited land for managing buying recyclable waste, unstable market conditions, no factory in Nay Pyi Taw and no definitive legislation or laws, seasonal changes are the main challenges for informal recycling shops. This study indicates the ways to mainstream the informal sectors in waste management schemes. In addition, the results of this study can be useful in developing national and regional waste management plans and programs.